The-chicken-and-egg dilemma - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Poultry By A J Smith, The Tropical Agriculturalist Series, Macmillan-CTA co-publication, second edition, 2001. 246 pp. ISBN 0 333 79149 5 CTA number 244. 10 credit points